Characterization of the immune profile of oral tongue squamous cell carcinomas with advancing disease. (8th May 2020) - Meehan, Katie; Leslie, Connull; Lucas, Michaela; Jacques, Angela; Mirzai, Bob; Lim, James; Bulsara, Max; Khan, Yasir; Wong, Nicholas C.; Solomon, Benjamin; Sader, Chady; Friedland, Peter; et al.
Abstract: We investigated whether a unique immune response was instigated with the development of oral tongue squamous cell carcinomas (OTSCC), with/without nodal involvement, with/without recurrent metastatic disease, or within tumor involved nodes. One hundred and ten formalin‐fixed paraffin‐embedded samples were collected from a retrospective cohort of 67 OTSCC patients and 10 non‐cancerous tongue samples. Targets including CD4, CD8, FOXP3, PD‐L1, and PD‐1 were analyzed by immunohistochemistry. The Nanostring PanCancer Immune Profiling Panel was used for gene expression profiling. Data were externally validated in the The Cancer Genome Atlas (TCGA) head and neck (HNSCC), melanoma and lung squamous cell carcinoma (LSCC) cohorts. A 24‐immune gene signature was identified that discriminated more aggressive OTSCC cases, and although not prognostic in HNSCC was associated with survival in other TCGA cohorts (improved survival for melanoma, P  < .001 and worse survival for LSCC, P  = .038). OTSCC exhibited concordant gene and immunohistochemical (IHC) features characterized by a TH‐2 biased, proinflammatory profile with upregulated B cell and neutrophil gene activity and increased CD4, FOXP3, and PD‐L1 expression ( P  < .001 for all by IHC). Compared to less advanced disease, nodal involvement and recurrent OTSCC did not induce a different immune response although recurrent disease was characterized by significantly higher PD‐L1 expression ( P  = .004 by SP263, P  = .013 by 22C3, P  = .004 for gene expression). Identification of a gene signature associated with different prognostic effects in other cancers highlights common pathways of immune dysregulation that are impacted by the tumor origin. The significant immunosuppressive signaling in OTSCC indicates primary failure of immune system to control carcinogenesis emphasizing the need for early, combination therapeutic approaches. Abstract : Oral tongue squamous cell carcinomas (OTSCC) exhibit primary immune failure to control carcinogenesis demonstrated by the absence of an immune response to the development of nodal metastases or recurrent disease. Proinflammatory immune gene expression is counteracted by immunosuppressive signaling mediated by FOXP3 and PD‐L1 expression. A gene signature was identified that was not prognostic in HNSCC but was significantly associated with survival in other cancers, demonstrating histotype‐dependent prognostic effects of immune regulation.